Effect of Heating treatment and Storage on The Hydroxymethylfurfural and pH in Iraqi Honey and Date molasses - Salman, Mohammed A.; Al-fekaiki , Dhia F.; Hameed, Sajjad A.; Mohammed, Lina S. (Basrah Journal Of Date Palm Research, 2024)
The study was conducted on different samples of Iraqi honey and molasses brought from local markets in Basra. The study included the effect of heating treatment and storage on the levels of hydroxymethylfurfural (HMF) and due to their importance in the quality of honey and molasses, The results showed significant differences between the averages. (P˂ 0.05). In both (HMF) and pH values. In honey samples, the highest value for (HMF) was 88.00 mg/kg in the heating treated mountain honey sample, and the lowest value was 14.01 mg/kg in processing honey. In molasses samples, the highest value for (HMF) a heating treatment processing molasses sample was 127.90, and the lowest value in a natural molasses 1 sample, was 25.89 mg/kg. The highest value for (HMF) with honey stored for a year was 100.11 mg/kg in local honey sample 1, and the lowest value in local honey 2 was 41.31 mg/kg. The pH values of honey and molasses samples, its highest value was in the heating treated molasses 2 sample, 5.31, and its lowest value was in the mountain honey sample, 3.1.